Penggunaan Konjungtor dalam Tugas Mahasiswa Ekonomi pada Mata Kuliah Bahasa Indonesia (MKU) Universitas Mahaputra Muhammad Yamin Solok - Wirasty, Rini (Jurusan PIPS FKIP UMMY Solok, 2016)
This research discusses about the use of conjunction on students’ assignments in the from of newspaper clippings. This study aims to determine the use of conjunction on newspaper. The method used in the study was a qualitative method that produces written data from the use of conjunction on studens' assgnments in the of clippings from local newspaper. Data collection techniques used wese (1) attached (clipping) on paper, (2) read clipping, (3) provide rencording, (4) classify the types of conjunction and (5) record all the data reganding the use of data analysis about conjunction. Techniques of analysis data wese (1) read the data, (2) classify the data, (3) discuss the data and (4) draw conclusions. Coordinative conjunctions include words dan, tetapi, serta, and atau. Subordinate conjunction incude the ketika, jika and kalau, agar and supaya. Based on the data above, coordinative conjunction was mostly used by using conjunction words dan meanwhile correlative conjunction was rarely to be used in the newspaper.